2022
DOI: 10.5713/ab.20.0749
|View full text |Cite
|
Sign up to set email alerts
|

The effect of multi-strain probiotics as feed additives on performance, immunity, expression of nutrient transporter genes and gut morphometry in broiler chickens

Abstract: The effect of multi-strain probiotics as feed additives on performance, immunity, expression of nutrient transporter genes and gut morphometry in broiler chickens

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Supplementing the diets of neonatal calves with probiotics can stimulate body growth 16,17 and organ development, 18 reduce the incidence of diarrhea, 17 and improve animal welfare and health, 19 providing long‐lasting benefits for sustainable milk production and metabolic profiling 20 . Studies in neonatal calves clearly reveal the importance of probiotic supplementation for improving the performance and health of Holstein calves 21,22 in terms of the immunity, expression of nutrient transporter genes, gut morphometry and microbiota of calves 17,23,24 . However, the effects of probiotics on small intestine development in neonatal calves have not been investigated thoroughly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementing the diets of neonatal calves with probiotics can stimulate body growth 16,17 and organ development, 18 reduce the incidence of diarrhea, 17 and improve animal welfare and health, 19 providing long‐lasting benefits for sustainable milk production and metabolic profiling 20 . Studies in neonatal calves clearly reveal the importance of probiotic supplementation for improving the performance and health of Holstein calves 21,22 in terms of the immunity, expression of nutrient transporter genes, gut morphometry and microbiota of calves 17,23,24 . However, the effects of probiotics on small intestine development in neonatal calves have not been investigated thoroughly.…”
Section: Introductionmentioning
confidence: 99%
“… 20 Studies in neonatal calves clearly reveal the importance of probiotic supplementation for improving the performance and health of Holstein calves 21 , 22 in terms of the immunity, expression of nutrient transporter genes, gut morphometry and microbiota of calves. 17 , 23 , 24 However, the effects of probiotics on small intestine development in neonatal calves have not been investigated thoroughly.…”
Section: Introductionmentioning
confidence: 99%
“…These results agreed with those of Pacifici et al ( 61 ), who reported that intra-amniotic administration of raffinose upregulated SGLT1 expression significantly. Similarly, dietary supplementation of multi-strain probiotics upregulated the expression of SGLT1 in broilers at 14 days post-hatch ( 81 ). The upregulated expression of brush-border membrane functional genes indicates the higher function and development of the small intestine and better nutrient absorption, leading to improving the growth performance of birds.…”
Section: Discussionmentioning
confidence: 99%
“…These supplements also contribute to eliminating the use of prophylactic drugs. The immunomodulating capabilities of these supplements are represented in several reports ( 9 , 75 , 81 ). TLR-2 is a pathogen recognition receptor expressed on infectious agents to recognize the molecular patterns associated with microbes and play a vital role in initiating and regulating the innate immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout history, Saccharomyces cerevisiae has been an indispensable fungus in agriculture and the food industry [1,2]. Besides the widespread and diverse applications of this yeast in various industries, a subtype of the species, namely S. 'boulardii' is applied commonly as a probiotic both for human use and even for livestock [3][4][5][6][7]. It is by far the leading probiotic yeast in the world [8] and its probiotic properties have been demonstrated in more than 80 randomized clinical trials for the strain S. 'boulardii' CNCM I-745 [6].…”
Section: Introductionmentioning
confidence: 99%